A Screen-Printed Electrode Modified With Graphene/Co3O4 Nanocomposite for Electrochemical Detection of Tramadol - Aflatoonian, Mohammad Reza; Tajik, Somayeh; Aflatoonian, Behnaz; Beitollahi, Hadi; Zhang, Kaiqiang; Le, Quyet Van; Cha, Joo Hwan; Jang, Ho Won; Shokouhimehr, Mohammadreza; Peng, Wanxi (Frontiers in Chemistry, 2020)
In this paper, graphene-based cobalt nanocomposite was synthesized and utilized for the development of a novel electrochemical sensor to detect tramadol. Tramadol determination was examined by cyclic voltammetry, differential pulse voltammetry, and chronoamperometry at graphene/Co3O4 nanocomposite-modified screen-printed electrode (G/Co3O4/SPE) in phosphate-buffered saline. Under the optimized condition, the detection limit of tramadol is 0.03 μM (S/N=3) in the linear ranges of 0.1–500.0 μM. Furtheremore, G/Co3O4/SPE was satisfactorily utilized to detect the spiked tramadol in tramadol tablet and urine specimens.